2007
DOI: 10.1002/bimj.200710382
|View full text |Cite
|
Sign up to set email alerts
|

A Note on P ‐values for Two‐sided Tests

Abstract: Based on uniformly most powerful unbiased (UMPU) tests for two-sided hypotheses and a short note in Lehmann (1959) on critical levels for randomized tests, Meulepas (1998, 1999) proposed (two-tailed) P -values taking into account the randomization constant(s) of the UMPU-tests. While UMPU-tests need an extra uniform observation if randomization is required, the P -values proposed by Meulepas need no extra uniform observation. At first glance, his idea looks very promising in order to define a suitable and powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…This has been demonstrated in Finner et al (2010) in the context of a discrete model with one-dimensional marginal parameters. A way out of this dilemma consists in usage of so-called "realized randomized p-values" as defined and explained by Finner and Straßburger (2007) and Finner et al (2010). Although they were originally derived in terms of randomized tests, we define them here in a more general way as follows.…”
Section: Realized Randomized P-valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been demonstrated in Finner et al (2010) in the context of a discrete model with one-dimensional marginal parameters. A way out of this dilemma consists in usage of so-called "realized randomized p-values" as defined and explained by Finner and Straßburger (2007) and Finner et al (2010). Although they were originally derived in terms of randomized tests, we define them here in a more general way as follows.…”
Section: Realized Randomized P-valuesmentioning
confidence: 99%
“…: Lehmann and Romano (2005). How to calculate p-values that are compatible with such tests is, however, a topic that is still vividly discussed in the scientific community, as the discussion of Finner and Straßburger (2007) and the recent works by Rüschendorf (2009) and Habiger and Peña (2011) show.…”
Section: Realized Randomized P-valuesmentioning
confidence: 99%
“…This means that, similar to non-randomized exact p-values introduced above, appropriately defined de-randomized p-values based on randomized UMPU tests are stochastically larger than U[0,1]-distributed random variables under the null hypothesis. An appropriate definition of de-randomized UMPU p-values can be found in [16] and is given as follows. Suppose X 2 = x 2 is observed.…”
Section: Tests Of Hwe and Corresponding P-valuesmentioning
confidence: 99%
“…Editor: Finner and Strassburger (2007) demonstrated that a randomized test (that relies on auxiliary randomization to determine rejection or non-rejection of the null hypothesis) can be more conservative than a de-randomized one. Yet this finding is not true for any meaningful comparison of a pair of corresponding tests.…”
mentioning
confidence: 99%
“…The issue is not the psychological comfort of the researcher, but rather what is best, at least in the case of clinical trials (admittedly not the application discussed by Finner and Strassburger, 2007), for the patients who rely on the results of the trials to inform their treatment decisions. If randomized tests are useful, then they should be used.…”
mentioning
confidence: 99%